MitraClip Therapy in Critically Ill Patients with Severe Functional Mitral Regurgitation and Refractory Heart Failure. Issue 4 (4th July 2019) - Turyan Medvedovsky, Anna; Tonchev, Ivaylo; Tahiroglu, Ilgar; Lotan, Chaim; Gilon, Dan; Planer, David; Danenberg, Haim D.; Beeri, Ronen; Shuvy, Mony
ABSTRACT: Background: The role of the MitraClip implantation in treatment of critically ill patients with heart failure and severe functional mitral regurgitation is undetermined. Methods: We screened all patients who underwent MitraClip implantation at the Hadassah Medical Center between October 2015 and December 2017. We evaluated immediate, 30-day and 1-year outcomes after the procedure in patients with refractory heart failure and severe functional mitral regurgitation, including patients with acute ischemic mitral regurgitation. Results: From a cohort of 64 patients, who underwent MitraClip implantation in our center, we identified six critically ill patients (9.4%) with decompensated refractory heart failure and severe functional mitral regurgitation (4+). Patients' mean age was 69.2 years, 67% were males. One, 2, or 3 clips were implanted in each case. Reduction of mitral regurgitation from grade 4+ to 1+ was achieved in 3 patients (50%), to grade 2+ in 2 patients (33.3%) with significant mean reduction of left atrial V-wave from 46.67 ± 8.50 mmHg to 21.67 ± 6.14 mmHg ( p = 0.009). Five patients were weaned from intravenous therapy and intra-aortic balloon pump support 24–72 hours after the procedure. One patient died during hospitalization due to sepsis. Thirty-day follow-up analysis showed improvement of NYHA functional class. Conclusions: MitraClip therapy could be a "bail-out" option in treatment of critically ill patients with refractory heart failure and severe functional mitral regurgitation.